Tissue fixed with formalin and processed without paraffin embedding is suitable for imaging of both peptides and lipids by MALDI‐IMS. Issue 11 (25th May 2016) - Pietrowska, Monika; Gawin, Marta; Polańska, Joanna; Widłak, Piotr
Abstract : Type and quality of sample preparation have significant impact on imaging mass spectrometry results. Though imaging of fresh‐frozen tissues is considered to give the best results, they are incompatible with clinical practice, since routine diagnostics is most frequently performed using formalin‐fixed tissues, and formalin‐fixed paraffin‐embedded material is a gold standard in histopathology. We aimed to assess utility of formalin‐fixed tissue specimen processed without paraffin embedding (i.e., deep‐frozen and cryo‐sectioned) for MALDI imaging of both peptides and lipids. Peptide and lipid imaging was performed in fresh‐frozen, FFPE and formalin‐fixed/frozen samples of a mouse kidney, then composition of the resulting spectra was compared. We demonstrated similarity of spectra registered during peptide imaging in FFPE and formalin‐fixed/frozen tissues, and similarity of spectra registered during lipid imaging in fresh‐frozen and formalin‐fixed/frozen material. Furthermore, molecular images of formalin‐fixed/frozen tissue resembled the features of both fresh‐frozen and FFPE tissue in the case of peptide imaging, and the features of fresh‐frozen tissue in the case of lipid imaging. We conclude that tissue preserved by formalin fixation and processed without paraffin embedding can be considered as an alternative to both fresh‐frozen and FFPE material.